Marchantia polymorpha, a New Model Plant for Autophagy Studies - Norizuki, Takuya; Kanazawa, Takehiko; Minamino, Naoki; Tsukaya, Hirokazu; Ueda, Takashi (Frontiers in Plant Science, 2019)
Autophagy is a catabolic process for bulk and selective degradation of cytoplasmic components in the vacuole/lysosome. In Saccharomyces cerevisiae, ATG genes were identified as essential genes for autophagy, and most ATG genes are highly conserved among eukaryotes, including plants. Although reverse genetic analyses have revealed that autophagy is involved in responses to abiotic and biotic stresses in land plants, our knowledge of its molecular mechanism remains limited. This limitation is partly because of the multiplication of some ATG genes, including ATG8, in widely used model plants such as Arabidopsis thaliana, which adds complexity to functional studies. Furthermore, due to limited information on the composition and functions of the ATG genes in basal land plants and charophytes, it remains unclear whether multiplication of ATG genes is associated with neofunctionalization of these genes. To gain insight into the diversification of ATG genes during plant evolution, we compared the composition of ATG genes in plants with a special focus on a liverwort and two charophytes, which have not previously been analyzed. Our results showed that the liverwort Marchantia polymorpha and the charophytes Klebsormidium nitens and Chara braunii harbor fundamental sets of ATG genes with low redundancy compared with those of A. thaliana and the moss Physcomitrella patens, suggesting that multiplication of ATG genes occurred during land plant evolution. We also attempted to establish an experimental system for analyzing autophagy in M. polymorpha. We generated transgenic plants expressing fluorescently tagged MpATG8 to observe its dynamics in M. polymorpha and produced autophagy-defective mutants by genome editing using the CRISPR/Cas9 system. These tools allowed us to demonstrate that MpATG8 is transported into the vacuole in an MpATG2-, MpATG5-, and MpATG7-dependent manner, suggesting that fluorescently tagged MpATG8 can be used as an autophagosome marker in M. polymorpha. M. polymorpha can provide a powerful system for studying the mechanisms and evolution of autophagy in plants.